Study of Several Stages of Maturity and Storage Temperature on Color Changes and Shelf Life of Mangosteen (Garcinia mangostana L.) - Inanpi Hidayati Sumiasih; Roedhy Poerwanto; Darda Efendi (International Journal of Applied Biology, 2019)
Color and freshness of mangosteen are important characters as benchmarks for consumers in the selection and purchase of mangosteen in the market. Color, freshness and shelf life of mangosteen are affected by the stage of maturity at harvest and the correct storage temperature. Information about the correct maturity stage for harvesting and storage temperature of mangosteen are needed by the mangosteen farmers, local merchant, and exporters as an effort to maintain the quality of fresh product. The objective of this research was to study the effect of several maturity stage at harvest and storage temperature to mangosteen color changes and shelf life during storage. The research used Completely Randomized Design of two factors. The first factor was the fruit maturity stage at harvest consisting of: Maturity Stage 1, 2, 3 and 4. The second factor was storage temperature of 15 oC and room temperature. The result of harvesting mangosteen at Maturity Stage 1 could maintain skin color longer than at Maturity Stage 2, 3, and 4. Mangosteens that were harvested at Maturity Stage 1 and 2, combined with storage temperature of 15 oC could maintain fruit quality up to 30 days after harvest and could be used for export market. While harvesting at Maturity Stage 3 could maintain fruit quality up to 25 days after harvest and Maturity Stage 4 up to 20 days after harvest. Harvesting at Maturity Stage 4 followed by 15 oC storage temperature and all Maturity stages combined with room temperature storage could be used for local market.Keyword: fruit color; horticultural commodities; queen of tropical fruits; shelf life